2022
DOI: 10.3390/ijerph19148687
|View full text |Cite
|
Sign up to set email alerts
|

Counseling for Physical Activity in Adults during the COVID-19 Pandemic: A Scope Review

Abstract: Objective: The aim of this scope review was to map the available scientific evidence on physical activity counseling for adults during the COVID-19 pandemic. Methods: The search was performed in PubMed, Web of Science, Scopus, SPORTDiscus, LILACS, SciELO, and CINAHL databases. Studies that described the population of adults over 18 years of age that used physical activity counseling during the COVID-19 pandemic context were selected. Data extracted were author, study location, sample, age group, sex, populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…There is also a growing body of research emerging from the COVID-19 pandemic and physical activity interventions that holds potential for research and implementation. For example, Gonçalves (2022) [39] conducted a scoping review and identified a growing interest in the transtheoretical model for recent intervention study designs and that general physical activity counselling interventions generally increased physical activities of participants.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a growing body of research emerging from the COVID-19 pandemic and physical activity interventions that holds potential for research and implementation. For example, Gonçalves (2022) [39] conducted a scoping review and identified a growing interest in the transtheoretical model for recent intervention study designs and that general physical activity counselling interventions generally increased physical activities of participants.…”
Section: Discussionmentioning
confidence: 99%